2020
DOI: 10.32322/jhsm.650925
|View full text |Cite
|
Sign up to set email alerts
|

Myomektomi uygulanan kadınlarda vücut kitle indeksi ile klinik parametreler arasındaki ilişkinin değerlendirilmesi

Abstract: Amaç: Abdominal myomektomi uygulanan kadınlarda vücut kitle indeksi ile klinik parametreler arasındaki ilişkiyi korelasyon analizi kullanarak değerlendirmek. Gereç ve Yöntem: Çalışmamıza abdominal myomektomi yapılan toplam 273 kadın dahil edildi. Hastalar vücut kitle indeksi (VKİ) 'ne göre (≤30 kg/m2 ve > 30 kg/m2) iki gruba ayrıldı. Yaş, VKİ, gravida, parite, myom çapı, preoperatif ve postoperatif hemoglobin (hb) düzeyleri, beyaz kan hücresi ve trombosit sayısı, nötrofil-lenfosit oranı (NLR), Ca125, Ca15-3 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Our study results are also not in line with the results of the study by Çoşkun et al [22] who found a positive correlation between BMI, Alpha-feto protein (AFP) levels and DOF, and a negative correlation between BMI, length of hospital stay and postoperative Hb level, and an association between BMI, bleeding requiring blood transfusion and increased complications after surgery. Amruta et al [23] found a direct association between BMI and the risk of fibroids, which does not support our study results.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study results are also not in line with the results of the study by Çoşkun et al [22] who found a positive correlation between BMI, Alpha-feto protein (AFP) levels and DOF, and a negative correlation between BMI, length of hospital stay and postoperative Hb level, and an association between BMI, bleeding requiring blood transfusion and increased complications after surgery. Amruta et al [23] found a direct association between BMI and the risk of fibroids, which does not support our study results.…”
Section: Discussioncontrasting
confidence: 99%